Forward together : a moral message for the nation. - Barber, William J., II, 1963- (St. Louis, Missouri : Chalice Press, 2014)
North Carolina's Moral Monday protests have drawn tens of thousands of protestors in what has been called the new Civil Rights Movement. Forward Together: A Moral Message for the Nation shares the theological foundation for the Moral Monday movement, serving as a proclamation of a new American movement seeking equal treatment and opportunity for all regardless of economic status, sexual preference, belief, race, geography, and any other discriminatory bases. The book will also serve as a model for other movements across the country and around the world using North Carolina as a case study, providing useful, practical tips about grassroots organizing and transformative leadership.
Print version record.
Includes bibliographical references and index.
Keywords: Christianity and politics -- North Carolina; Christianity and politics -- United States; Church and social problems -- North Carolina; Church and social problems -- United States; North Carolina -- Moral conditions; United States -- Moral conditions; RELIGION -- Ethics; Christianity and politics; Church and social problems; Moral conditions; North Carolina; United States; RELIGION / Christianity / History; Electronic books